Foreign languages education in international literary festival tourism: the case of Festivaletteratura in Italy. - ROSSETTI, GIULIA (International Journal of Language, Translation and Intercultural Communication, 2016)
Festivals have always represented a good opportunity on the economic front, but most importantly they have been perfect occasions for creating settings for social, cultural and inter-linguistic interaction. Nowadays, thanks to the globalisation process, intercultural and inter-lingual communications are increasingly important in the festivals domain, especially those focused on international literary events. According to the experiential learning theory, international book festivals can be environments for learning activities, and specifically for language development. Thus, these cultural events have provoked such questions as the following: attending international literary festivals can increase participants’ language learning? In what ways do international literary festival managers invest in multilingual services in order to encourage language learning? This study aims to investigate if international literary festivals can develop adult visitors’ language learning, taking Festivaletteratura of Mantua (Italy) as a case study. Firstly, I shall present the importance of interlingual communication in festival tourism and the experiential learnign theory. Secondly, I will explore Festivaletteratura supply analysis, considering also its international projects as potential language training tools: Scritture Giovani and Vocabolario Europeo, and Festivaletteratura’s international connection with other partners: the Hay Festival and the Berlin Internationales Literaturfestival. Then, I will investigate the role of foreign languages in the demand analysis of the festival, according to the questionnaire survey among 300 adult attendees during the 2015 Festivaletteratura edition. Finally, I intend to argue that even if the festival might provide a setting for language learning with lots of international guests, due to its target, who is not familiar with foreign languages, it cannot be described as an example of language learning environment.